FEMALE GENDER AS AN ADDITIONAL RISK FACTOR FOR ATHEROTHROMBOTIC COMPLICATIONS OF IHD - Netyazhenko, V.Z.; Netyazhenko, N.V.; Malchevska, T.Y.; Plienova, O.M. (World of Medicine and Biology, 2018)
A comparative evaluation of the state of thrombocyte-plasma haemostasis was performed in patients of both sexes with acute and chronic forms of ischemic heart disease. It was found that women of all compared groups showed high platelet and procoagulant activity in comparison with men, despite the use of antiaggregant therapy and anticoagulants. MI in women is more unfavorable with increasing frequency of atrial fibrillation paroxysms and Lown III-IV extrasystolic arrhythmia (by 11.4% and 10.0%), cardiogenic shock by 6.8%, early postinfarction angina and pulmonary edema by 5 % compared to men. The delay in interventional intervention is associated with a 2.7-fold increase in mortality in women compared to men. A postmenopausal period of up to 5 years should be considered as an independent predictor of cardiovascular events. The postmenopausal period lasting less than 5 years in women with stable ischemic heart disease is accompanied by prothrombotic and procoagulant shifts of platelet-plasma hemostasis, even with antiplatelet treatment and is associated with an increase in the risk of adverse course of probable MI 7.1-fold (OR 7.1, 95% CI, 6-9.2, p = 0.046).
Keywords: thrombotic complications; atherosclerosis; women; ischemia